2017
DOI: 10.1021/acscatal.7b02402
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium–Tin Binary Nanoparticle—A Strategy to Develop an Alternative Electrocatalyst for Oxygen Reduction

Abstract: A Rh−Sn nanoparticle is achieved by combinatorial approaches for application as an active and stable electrocatalyst in the oxygen reduction reaction. Both metallic Rh and metallic Sn exhibit activities too low to be utilized for electrocatalytic reduction of oxygen. However, a clean and active Rh surface can be activated by incorporation of Sn into a Rh nanoparticle through the combined effects of lateral repulsion, bifunctional mechanism, and electronic modification. The corrosion-resistant property of Rh co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…For instance, non-Pt catalysts such as Pd–Rh, Au–Rh, Rh–Sn, etc. could deliver a mass-specific activity of ∼0.20 A/mg, which is far below the target value. During the course of the present investigation, Li et al demonstrated the ORR and formic acid oxidation reaction (FAOR) activity of Pd-based trimetallic alloy catalyst at two different pHs (alkaline and acidic) . Zuo et al reported the ORR and ethanol oxidation activity of Pd-based alloy electrocatalyst in acidic and alkaline pH, respectively .…”
Section: Introductionmentioning
confidence: 74%
“…For instance, non-Pt catalysts such as Pd–Rh, Au–Rh, Rh–Sn, etc. could deliver a mass-specific activity of ∼0.20 A/mg, which is far below the target value. During the course of the present investigation, Li et al demonstrated the ORR and formic acid oxidation reaction (FAOR) activity of Pd-based trimetallic alloy catalyst at two different pHs (alkaline and acidic) . Zuo et al reported the ORR and ethanol oxidation activity of Pd-based alloy electrocatalyst in acidic and alkaline pH, respectively .…”
Section: Introductionmentioning
confidence: 74%
“…Here, we first investigate whether this electron interaction also exists between SWNTs and an appropriate metal. Metallic rhodium (Rh) has a high catalytic property for many reactions, and recent studies show the Rh-based electrocatalysts may be more active than Pt for the HER and ORR. Therefore, with attempts to explored novel catalysts for enhanced electrocatalysis, the electronic structures and interface interaction between Rh and SWNTs were intensely evaluated. In the combination of Rh and SWNTs, SWNTs would draw the electrons to deviate from Rh by a noncovalent effect.…”
Section: Introductionmentioning
confidence: 99%
“…The inexpensive GO-based active and stable catalysts combined with tiny Rh nanospheres (NSs) are used to moderate the cost-effectiveness of that electrocatalyst. 23 The nanocatalyst shows an important role in succeeding highly effective electrocatalysts, and it has been used to facilitate remarkable performance for splitting of water by HERs and OERs. It is used as an alternative to Pt because GO-based Rh at its nanoscale reduces the overall utilization; hence, it controls the cost.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This newly designed electrocatalytic system is promising for industrial and commercial applications in the large-scale production of H 2 as a fuel via both HERs and OERs, respectively. The inexpensive GO-based active and stable catalysts combined with tiny Rh nanospheres (NSs) are used to moderate the cost-effectiveness of that electrocatalyst . The nanocatalyst shows an important role in succeeding highly effective electrocatalysts, and it has been used to facilitate remarkable performance for splitting of water by HERs and OERs.…”
Section: Introductionmentioning
confidence: 99%